Factors Associated with Vitamin A Consumption in Postpartum Mothers in Lubuk Buaya Community Health Center, Padang City - Novi Maya Sari; Dewi Eka Stia Murni; Yayuk Sri Rahayu; Sari Ida Miharti; Suyati (Bulletin of Inspiring Developments and Achievements in Midwifery, 2025)
Vitamin A deficiency remains a significant public health issue impacting maternal and child health, particularly in developing countries. This study aimed to examine factors influencing vitamin A capsule consumption among postpartum mothers at Lubuk Buaya Community Health Center (Puskesmas), Padang City. A cross-sectional analytical survey was conducted on 57 postpartum mothers selected using purposive sampling. Data were collected using a valid and reliable questionnaire, and analyzed with chi-square tests at a 0.05 significance level. The study found that 56.1% of respondents did not consume vitamin A capsules. Education level and knowledge significantly influenced consumption behavior (education: p=0.000; knowledge: p=0.003), with mothers having higher education and better knowledge more likely to consume vitamin A. However, the role of health workers did not show a significant effect (p=0.855). These findings indicate that increasing education and improving health literacy should be prioritized in strategies to boost vitamin A consumption among postpartum mothers. Health interventions need to focus on nutrition education and active community involvement to ensure better health outcomes and meet national vitamin A supplementation goals.